EFEKTIVITAS DIGITALISASI PELAYANAN PUBLIK MELALUI APLIKASI DIGITAL KORLANTAS POLRI - , Herbrian Kurnia Alam; Hanny Purnamasari (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
he government, as the organizer of the state, has the obligation to provide public services that are effective and efficient. The Indonesian National Police has a duty, one of which is to serve the public by managing motor vehicle registration documents. To support public services, the Indonesian National Police has created a digital application for the Traffic Corps to facilitate online services for the community, featuring various services such as SINAR (National Precision SIM), SIGNAL (National Digital Samsat), ETLE (Electronic Traffic Management), and NTMC Polri. The aim of this research is to determine the effectiveness of the digitalization of public services using the Korlantas Digital Application to enhance services for the community. The research approach is descriptive, utilizing qualitative methods and data collection techniques through literature studies from articles and journals. This study employs Duncan's Effectiveness Theory with three dimensions: goal achievement, integration, and adaptation. Research results indicate that currently, the only feature available for the public is the service for extending driver's licenses. However, the use of this application is quite effective in facilitating services for those who do not have the time to visit the Driver's License Administration Unit (Satpas) in person, and it serves as a response from the Indonesian National Police regarding public services that often encounter issues during the processing of motor vehicles.